Implementasi Edukasi Agribisnis Kopi di Dong Phu Vietnam sebagai Penguatan Praktik Petani Indonesia: Pengabdian - Mitra Musika Lubis; Ihsan Effendi; Retna Astuti Kuswardani M.S (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This international Community Service (CSP) program was conducted in Dong Phu District, Binh Phuoc Province, Vietnam. The main objective of the program was to strengthen the capacity of Indonesian coffee farmers through knowledge transfer regarding Vietnamese coffee agribusiness practices that have proven efficient, standardized, and supported by strong cooperative institutions. Implementation methods included technical education, workshops, field observations, post-harvest demonstrations, focus group discussions, and the development of follow-up plans. The program produced nine outputs (W1–W9), including training modules, practical videos, harvest quality standards leaflets, documentation, a draft cooperation agreement, an agribusiness flow map, program evaluation, and a six-month follow-up plan. Evaluation through pre-post tests showed a significant increase in participants' knowledge, particularly in cultivation techniques, selective harvesting, wet sorting, fermentation, gradual drying, and export quality standards. This program successfully established an initial Indonesia–Vietnam network and developed a coffee agribusiness learning model that can be replicated in Indonesia.